2023
DOI: 10.1021/acsomega.2c06881
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Cellulose Acetate Nanofibrous Scaffolds with Retinyl Palmitate and Clove Essential Oil for Wound Healing Applications

Abstract: The use of biocompatible materials and fabrication methods is of particular importance in the development of wound dressings. Cellulose acetate (CA) has excellent properties for wound dressing applications, but it is insufficient for the wound healing process due to its lack of bioactive and antibacterial properties. In this study, CA was electrospun with retinyl palmitate (RP) and clove essential oil (CLV) to fabricate a novel antibacterial and antioxidant biomaterial. The effects of RP and CLV incorporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…The antibacterial activity of nanofiber membranes was also analyzed quantitatively by the OD technique as described by Akturk (2023) . Tubes without nanofiber samples were used as the control.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…The antibacterial activity of nanofiber membranes was also analyzed quantitatively by the OD technique as described by Akturk (2023) . Tubes without nanofiber samples were used as the control.…”
Section: Methodssupporting
confidence: 92%
“…The antibacterial activity of nanofiber membranes was also analyzed quantitatively by the OD technique as described by Akturk (2023). 22 Tubes without nanofiber samples were used as the control. After incubation, the absorbance of the nutrient broth solutions was measured at 600 nm by using a UV–vis spectrophotometer (BioTek Synergy HT).…”
Section: Methodsmentioning
confidence: 99%
“…The results demonstrate a similar activity against S. aureus and C. albicans (MIC of 2 mg/mL) and a slightly better activity against E. coli (MIC of 1.78 mg/mL). The obtained data are similar to those reported in the literature [57,80,81] and can be explained by the different composition of their cell wall structures that distinguish Gram-positive from Gram-negative bacteria. The disc diffusion method showed that CS/OP hydrogels without CO did not inhibit the growth of the three selected bacteria and fungi strains (Figure S5).…”
Section: Antibacterial Assaysupporting
confidence: 89%
“…The antimicrobial and antifungal effects of the hydrogels against total viable bacteria (Log CFU/mL) were measured after incubation of bacterial strains at a density of 1.5 × 10 8 CFU/mL in the presence of hydrogels for different periods. As the results show (Figure 10), the effectiveness of the CS/OPx-Cy hydrogels was better against E. coli than S. aureus, similar to that of free CO, due to the different composition of the cell wall structure [57,80]. All hydrogels provided a significant reduction in the bacterial number indicating their good antibacterial activity.…”
Section: Antibacterial Assaymentioning
confidence: 93%
“…The cell viability (expressed in%) observed with the varying extract concentrations was 103.35 ± 3.72 for PCL/BG/5PPE, 95.52 ± 3.16 for PCL/BG/10PPE, and 85.23 ± 5.66 for PCL/BG/15PPE. In accordance with EN ISO-10993-5/12, cell viability greater than 80% is classified as non-toxic [35,36]. The viability of the L929 cells incubated at all the extract concentrations was above 80%.…”
Section: Cytotoxicity Of Scaffoldsmentioning
confidence: 85%